Burnout and Satisfaction With Work–Life Integration Among Nurses. Issue 8 (August 2019) - Dyrbye, Liselotte N.; West, Colin P.; Johnson, Pamela O.; Cipriano, Pamela F.; Beatty, Dale E.; Peterson, Cheryl; Major-Elechi, Brittny; Shanafelt, Tait
Abstract : Objectives: To evaluate characteristics associated with burnout and satisfaction with work–life integration (WLI) among nurses and compare their experience to other American workers. Methods: We used data from 8638 nurses and 5198 workers to evaluate factors associated with burnout and satisfaction with WLI, and compare nurses to workers in other fields. Results: In the multivariable analysis, demographics, work hours, and highest academic degree obtained related to nursing were independent predictors of burnout. Factors independently associated with satisfaction with WLI included work hours. In pooled multivariable analyses including nurses and other workers, nurses were not more likely to have symptoms of burnout but were more likely to have lower satisfaction with WLI. Conclusions: Work hours and professional development related to the risk of burnout among nurses. Nurses are at similar risk for burnout relative to other US workers but experience greater struggles with WLI. Abstract : Supplemental Digital Content is available in the text